Sampling and tracking a changing environment: persistence and reward in the foraging decisions of bumblebees. Issue 3 (21st April 2017) - Dunlap, Aimee S.; Papaj, Daniel R.; Dornhaus, Anna
Abstract : The question of when to collect new information and how to apply that information is central to much of behaviour. Theory suggests that the value of collecting information, or sampling, depends on environmental persistence and on the relative costs of making wrong decisions. However, empirical tests of how these variables interact are lacking. We tested whether bumblebee foraging decisions are indeed influenced by these two factors. We gave bees repeated choices between a resource providing a steady, mediocre reward and a resource fluctuating between a low reward and a high reward. In this paradigm, we manipulated environmental persistence by changing how long the quality of a fluctuating resource remained stable at one reward level. We manipulated the costs of decision errors by changing the relative values of the available rewards. Bees sampled the fluctuating resource more frequently when it changed quality more frequently, indicating that they measured environmental persistence and reacted to it as predicted by theory. Bees showed surprisingly suboptimal tracking, not reliably choosing the currently best resource except when the fluctuating resource was very persistent and the potential rewards high. While bees modify their choices in response to different levels of change and potential rewards, they do not always do so according to optimality predictions.